Comparison of effects of training order of explosive strength and plyometrics training on different physical abilities in adolescent handball players - van den Tillaar, R.; Roaas, T. V.; Oranchuk, D. (Biology of Sport, 2020)
While both plyometric and traditional resistance training methods are beneficial to athletic performance in a wide range of sports, their efficacy regarding training order has yet to be determined in a periodized training programme. Therefore, this study compared the effects of a 12-week training period where explosive strength training (six weeks) preceded plyometric training (six weeks), or vice versa. Forty-two competitive male (n = 12) and female (n = 30) adolescent handball players (age 14.9 ± 0.5 years, body mass 64.1 ± 9.1 kg, height 1.71 ± 0.09 m) conducted explosive strength training for six weeks followed by six weeks of plyometric training or vice versa. Variables included a 30 m sprint, a change of direction test, countermovement jump (CMJ) with and without arm swing, load-velocity back squat assessment, overhead throwing velocity with and without preliminary steps, and the Yo-Yo intermittent recovery test level 1 (Yo-Yo IR1). Both groups experienced similar improvements in the CMJ, change of direction and load-velocity squat assessments from pre- to posttest (p = 0.013, ?2 = 0.194-0.378). Conversely, no improvements were observed in the Yo-Yo IR1, 30 m sprint or throwing velocity tests, regardless of group (p = 0.081). No main effect of training order was observed for any of the tests employed (p = 0.31). Training order does not appear to play a noticeable role in the physical development of young handball players. Therefore, practitioners could focus on implementing variations in exercise and loading to benefit athlete adherence and correspond to present needs.